(3GdOdjd GdeQLYj GdYQHj dNOeGJ EOGQI GdHjGfGJ GdHMKjI aj GdecJHGJ GdCcGOjejI hGdeJNUUIs - (3UGdM, YeGO YjSis; (3GdMQGUj, fHgGf Hf MGQKs; (3GdRGed, efhQ YHO Gddgs; (3GdSjO, CeGfj eMeOs ((3YeGf, GdCQOfs (3OGQ GHf QTjb ddfTQ hGdJhRjYs, 2025)
(3jJfGhd GdcJGH ehVhY GdHjGfGJ GdHMKjI hCgejJgG hCfgG eMhQG CSGSjG aj efXheI GdHMK GdYdej deG dg CgejI aj OYe GdGHJcGQ, hJYRjR GdTaGajI, hVeGf GSJOGeI GdeYQaI(B. (3hJYO GdecJHGJ GdCcGOjejI GdCbQH Edi gPG GdeLGd HMce ehbYgG aj bdH GdLGeYGJ hGdcdjGJ GdYdejIs
(3cJGH deDJeQ GdGJMGO GdYQHj ddecJHGJ hGdeYdheGJ CYde (B2025 (3GdPj JSJVjag ecJHI bWQ GdhWfjIs
Keywords: (3GdHjGfGJs -- (3EOGQIs; (3GdecJHGJs -- (3EOGQIs